Mucins and their receptors in chronic lung disease. Issue 3 (17th March 2020) - Denneny, Emma; Sahota, Jagdeep; Beatson, Richard; Thornton, David; Burchell, Joy; Porter, Joanna
Abstract: There is growing recognition that mucus and mucin biology have a considerable impact on respiratory health, and subsequent global morbidity and mortality. Mucins play a critical role in chronic lung disease, not only by providing a physical barrier and clearing pathogens, but also in immune homeostasis. The aim of this review is to familiarise the reader with the role of mucins in both lung health and disease, with particular focus on function in immunity, infection and inflammation. We will also discuss their receptors, termed glycan‐binding proteins, and how they provide an attractive prospect for therapeutic intervention. Abstract : This review article explores the role of mucins in respiratory health and disease, with particular focus on their receptors, the glycan‐binding proteins.